2016
DOI: 10.1111/exd.13115
|View full text |Cite
|
Sign up to set email alerts
|

IL‐17A promotes neutrophilic inflammation and disturbs acute wound healing in skin

Abstract: In the wound healing process, neutrophils are the first inflammatory cells to move to the wound tissues. They sterilize wounds by killing microbes, and they stimulate other immune cells to protect the host from infection. In contrast, neutrophil-derived proteases cause damage to host tissues, so neutrophils play dual opposite roles in wound healing. Interleukin-17A (IL-17A) is a proinflammatory cytokine that promotes the recruitment of these cells. The role of this cytokine in the wound healing process is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 46 publications
5
44
0
5
Order By: Relevance
“…A study by Tagaki et al revealed that IL-17A knockout mice had enhanced wound closure, collagen deposition and myofibroblast differentiation. In contrast, exogenous supplementation of IL-17 resulted in increased infiltration of neutrophils, lessened deposition of collagen and delayed wound closure [47]. Similarly, our study depicted an increased expression of Cox-2 and IL-17 upon BMSCTx in mice that was abrogated in the presence of celecoxib leading to enhanced engraftment of stem cells and wound closure.These results prompted us to elucidate the downstream mechanisms involved in Cox-2-mediated inflammation through IL-17.…”
Section: Discussionsupporting
confidence: 65%
“…A study by Tagaki et al revealed that IL-17A knockout mice had enhanced wound closure, collagen deposition and myofibroblast differentiation. In contrast, exogenous supplementation of IL-17 resulted in increased infiltration of neutrophils, lessened deposition of collagen and delayed wound closure [47]. Similarly, our study depicted an increased expression of Cox-2 and IL-17 upon BMSCTx in mice that was abrogated in the presence of celecoxib leading to enhanced engraftment of stem cells and wound closure.These results prompted us to elucidate the downstream mechanisms involved in Cox-2-mediated inflammation through IL-17.…”
Section: Discussionsupporting
confidence: 65%
“…Finally, IL‐17 and TNF‐α are reported to sustain neutrophil recruitment. The detrimental effects of neutrophils have also been previously reported (19), where neutrophil‐depleted mice had a significant improvement in acute wound closure. Both IL‐23 and IL‐17 deficiency resulted in reduced neutrophil numbers.…”
Section: Discussionsupporting
confidence: 60%
“…There is some discrepancy about the source of IL‐17 produced in the skin, with reports showing that macrophages, neutrophils, γδ Tcells, and T helper(T h )17 cells are able to express IL‐17 (12, 19, 20). Using a reporter mouse model, we labeled any cell that activated the promoter for IL‐17A with yellow fluorescent protein.…”
Section: Resultsmentioning
confidence: 99%
“…Interleukin-17A is a proinflammatory cytokine that promotes the recruitment of neutrophils during wound healing. In wound healing, it likely delays wound healing while enhancing an inflammatory response that would promote the removal of microbes [117]. TRAF3IP2 alters keratinocyte differentiation in the skin and inhibits response to IL-17 [118].…”
Section: Calcium Signaling and Inflammation Related Genesmentioning
confidence: 99%